THE EFFECT OF SPECIAL AUTONOMY FUNDS, REGIONAL ORIGINAL REVENUE AND LOCAL GOVERNMENT EXPENDITURES ON WELFARE IN PAPUA PROVINCE - Fadhil Firmansyah; Saparuddin Mukhtar; Karuniana Dianta Arfiando Sebayang (Yayasan Education and Social Center, 2022)
This study examines the effect of the Special Autonomy Fund, PAD and Government Expenditures on the Welfare of 19 Regencies/Cities in Papua Province with the Human Development Index as a reference for their welfare. This approach to research employs descriptive quantitative techniques based on correlation. Panel data from 2015-2021 and a cross-section of 19 regencies/cities in Papua Province gathered using document data collection techniques were used to compile the data for this study. To analyze the data in this study using multiple regression analysis with the help of the Econometric application Views (Eviews 10). The results of this study indicate that the Special Autonomy Fund variable significantly negatively affects the Human Development Index. Meanwhile, the Regional Original Income variable has a positive and insignificant effect on the Human Development Index. Next, the Regional Government Expenditure variable has a significant positive effect on the Human Development Index. Simultaneously, all variables positively and significantly affect the Human Development Index in Papua Province. For R2 in this study, the independent variable could explain the dependent variable of 97.27% and the remaining 2.73% was influenced by other factors